2013
DOI: 10.1590/s0100-736x2013000700002
|View full text |Cite
|
Sign up to set email alerts
|

Torque teno sus virus (TTSuV) infection at different stages of pig production cycle

Abstract: Pesq. Vet. Bras. 33 (7) It has been demonstrated that TTSuV might increase the severity of other important viral diseases with economic and public health impacts. At present, there is no information on the age distribution of pigs infected with TTSuV in Brazilian herds. This study evaluated the frequency of TTSuV infection in pigs at different stages of production. Fecal samples (n=190) from pigs at 1 to 24 weeks of age and from breeders at 6 farrow-to-weaning (up to 8 weeks of age) and 9 grower-to-finish (9 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Coinfections of multiple genetically diverse anelloviruses have been reported in in humans (Okamoto et al, 1999) and also other mammals several studies (Biagini et al, 2007;Fahsbender et al, 2017;Huang et al, 2010;Kraberger et al, 2020b;Leme et al, 2013;Nishiyama et al, 2014). This was also evident for the feline TTFVs where blood samples from 17 individuals harboured between two and four distinct anellovirus species (Table 1).…”
Section: Co-infection Dynamicsmentioning
confidence: 59%
“…Coinfections of multiple genetically diverse anelloviruses have been reported in in humans (Okamoto et al, 1999) and also other mammals several studies (Biagini et al, 2007;Fahsbender et al, 2017;Huang et al, 2010;Kraberger et al, 2020b;Leme et al, 2013;Nishiyama et al, 2014). This was also evident for the feline TTFVs where blood samples from 17 individuals harboured between two and four distinct anellovirus species (Table 1).…”
Section: Co-infection Dynamicsmentioning
confidence: 59%
“…The fecal–oral route is assumed to be the main route of infection for anelloviruses, but they are also transmitted by vertical and transplacental/intra-uterine route [ 33 , 34 ]. A Brazilian study showed similar results, suggesting that TTSuV detected in fecal samples spread to pigs of all production stages and that the viral infection rate increased with the age of the animals [ 35 ]. Similar to Blois et al [ 15 ], we could not find a difference between males and females concerning TTSuV1 prevalence.…”
Section: Discussionmentioning
confidence: 84%
“…On the other hand, TV-A, SV-A, and EV-G RNA detection in solid fecal samples could indicate that porcine enteric picornaviruses were not always associated with the occurrence of diarrhea in this study. To properly assess the association of the virus's presence with the occurrence of diarrhea, it is necessary to design a specific investigation, including the evaluation of infections with other porcine enteric viruses, such as rotaviruses, caliciviruses, picobirnavirus, Aichivirus C, Senecavirus A, and Torque teno sus virus, which are endemic in Brazilian pig herds [24,[29][30][31][32][33][34][35][36][37][38].…”
Section: Responsible Editor: Fernando Spilkimentioning
confidence: 99%